2008
DOI: 10.1159/000128978
|View full text |Cite
|
Sign up to set email alerts
|

Medial Olivocochlear Functioning and Speech Perception in Noise in Older Adults

Abstract: The purposes of this study were to: (1) compare medial olivocochlear system (MOCS) functioning and speech perception in noise in young and older adults and (2) to quantify the correlation between MOCS functioning and speech perception in noise. Measurements were taken in 20 young (mean 26.3 ± 2.1 years) and 20 older adults (mean 55.2 ± 2.8 years). Contralateral distortion product otoacoustic emission (DPOAE) suppression was measured to assess MOCS functioning. Speech perception in noise was evaluated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 72 publications
5
29
1
Order By: Relevance
“…One of these (27) also found reduced activation in the bilateral superior temporal gyrus in members of their older sample. A similar study (28) reported that decline in medial olivocochlear function might explain the poorer speech perception in noise observed in elderly listeners. The present outcomes, together with these recent reports, suggest a need for deliberate research strategies and designs to investigate further the impact of bilateral implantation as a function of chronological age.…”
Section: Discussionmentioning
confidence: 82%
“…One of these (27) also found reduced activation in the bilateral superior temporal gyrus in members of their older sample. A similar study (28) reported that decline in medial olivocochlear function might explain the poorer speech perception in noise observed in elderly listeners. The present outcomes, together with these recent reports, suggest a need for deliberate research strategies and designs to investigate further the impact of bilateral implantation as a function of chronological age.…”
Section: Discussionmentioning
confidence: 82%
“…Several extensions to cochlear models (Messing, Delhorne, Bruckert, Braida, and Ghitza, 2009;Brown, Ferry, and Meddis, 2010) have been proposed for mimicking the MOC reflex, and these models have shown that better automatic speech recognition performance in noise can be achieved when the MOC model is incorporated into the cochlear model. However, there have been reports by others who have not observed a correlation of speech intelligibility with the olivocochlear reflex (Wagner, Frey, Heppelmann, Plontke, and Zenner, 2008;Mukari and Mamat, 2008). Transient evoked (TE) and stimulus frequency evoked (SF) OAEs at low and moderate stimulus levels are thought to be generated by a linear coherent reflection of the forward traveling wave near the tonotopic peak region (Zweig and Shera, 1995;Kalluri and Shera, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This also suggests a slightly immature pattern of SSOAEs frequency distribution exists in 2-to 4 -day-old neonates, and implies that the OHCs should still be undergoing functional regulation after birth. But, we should note that Braun's study contained data from adults with a large span of age ranges, and some of the adults were at an age where their OHCs have already begun to degenerate [25].…”
Section: Discussionmentioning
confidence: 99%